Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Sunday, May 26, 2013 at 10:58pm.

- Mathematics -
**Anonymous**, Monday, May 27, 2013 at 2:45am-6x=3x

-6x-3x=?

-9x

- Mathematics -
**a**, Monday, May 27, 2013 at 8:10amyes

**Related Questions**

math - 3x-4=-2(3x+5) 3x-4=-2(3x+5) clear the fraction. 3x-4=-6x-10 add+6x+4 to ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

Math- Adv. Alg. w/ Trig. - I need help simplifying this expression: (3x^3y^5 + ...

Math - Can someone please check my answers below for accurateness? The ...

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...

math - simplify (x^2-3x+6)-(36x^2-18x+6/6) (x^2-3x+6)-(6(6x^2-3x+1/6) cancel the...

math,help - Is this trinomial a perfect square x^2-6x+9 if the trinomial starts ...

Mathematics - If 1-x -2x -3x = 6x-1 what is the value of x?

Math - Differentiate g(x)=(x^3+1)(3x^2-1) so I use g'(x) X h(x) + g(x) X h'(x) ...

calculus - Find the derivative using the chain rule. f(x) = ((3x-7)/(6x+3))^4 f...